KORELASI INDEKS MASSA TUBUH DAN WAIST HIP RATIO DENGAN PROFIL LIPID SERUM - Reynold Andika Yohanata; Triawanti Triawanti; Azma Rosida (Homeostasis, 2019)
Abstract: Lipid profile consist of total cholesterol, Low Density Lipoprotein cholesterol, High Density Lipoprotein cholesterol, and triglyceride. Lipid profile can be influenced by several factors, and one of them is obesity. Obesity is determined by Body Mass Index (BMI) and Waist Hip Ratio (WHR). The purpose of this study was to see the correlation of BMI and WHR on levels of serum LDL-C, HDL-C, and TG in obese patients in the working area of Puskesmas Pekauman. This study was an observational analytic study with a cross sectional approach. The population of this study was obese patients in Puskesmas Pekauman, the sample size was 51 people with a consecutive sampling technique. The data obtained were analyzed using bivariate analysis. The results of bivariate analysis with Pearson correlation test found that BMI and WHR did not have a significant correlation with levels of K-LDL, K-HDL, and serum TG (p>0,05). The conclusion of this study is that BMI and WHR did not have a significant correlation with levels of serum LDL-C, HDL-C, and TG in obese patients in the working area of Puskesmas Pekauman. Keywords: Body Mass Index, Waist Hip Ratio, obesity, serum lipid profile Abstrak: Profil lipid terdiri dari kadar kolesterol total, kolesterol Low Density Lipoprotein, kolesterol High Density Lipoprotein, dan trigliserida. Profil lipid dipengaruhi oleh beberapa faktor, salah satunya yaitu obesitas. Obesitas ditentukan oleh Indeks Massa Tubuh (IMT) dan Waist Hip Ratio (WHR). Tujuan penelitian ini untuk melihat korelasi IMT dan WHR terhadap kadar K-LDL, K-HDL, dan TG serum pada penderita obesitas di wilayah kerja Puskesmas Pekauman. Penelitian ini merupakan penelitian observasional bersifat analitik dengan pendekatan cross sectional. Populasi penelitian ini adalah penderita obesitas di Puskesmas Pekauman, besar sampel berjumlah 51 orang dengan teknik pengambilan sampel secara consecutive sampling. Data dianalisis menggunakan analisis bivariat. Hasil analisis bivariat dengan uji korelasi Pearson didapatkan bahwa IMT dan WHR tidak memiliki korelasi bermakna dengan kadar K-LDL, K-HDL, dan TG serum (p>0,05). Kesimpulan penelitian didapatkan IMT dan WHR tidak memiliki korelasi yang bermakna dengan kadar K-LDL, K-HDL, dan TG serum pada penderita obesitas di wilayah kerja Puskesmas Pekauman. Kata-kata kunci: Indeks Massa Tubuh, Waist Hip Ratio, obesitas, profil lipid serum